Retropharyngeal Calcific Tendinitis Mimicking a Retropharyngeal Phlegmon. (3rd June 2013) - Gabra, Nathalie; Belair, Manon; Ayad, Tareck
Abstract : Background . Acute retropharyngeal tendinitis is a little known but not an uncommon condition. It was first described by Hartley in 1964 as an inflammation of the longus colli muscle secondary to calcium crystals deposition on its insertion. The calcifications are mostly located on the oblique portion of the muscle at the level of C1-C2. Methods . We will describe this disease through 4 cases that presented in our institution. Results . The most common symptoms are severe neck pain, odynophagia, and a painful restriction of neck movement. It is associated with mild fever and inflammatory lab findings such as a slight elevation of white blood cell count, erythrocyte sedimentation rate, and C-reactive protein. CT scan is recommended as the first-line imaging modality to establish a diagnosis. Treatments consist of NSAIDs and analgesics to accelerate the healing process. If symptoms are severe, a course of corticosteroids is required. Conclusion . Since the clinical and laboratory findings of this condition and those of a retropharyngeal abscess overlap, it is important to establish the right diagnosis in order to prevent more invasive procedures. A good knowledge of this clinical entity by otolaryngologists would prevent delays in hospital discharge and unnecessary anxiety.